2014
DOI: 10.2522/ptj.20130095
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Response Relationship Between Cumulative Lifting Load and Lumbar Disk Degeneration Based on Magnetic Resonance Imaging Findings

Abstract: The results suggest a dose-response relationship between cumulative lifting load and LDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…They showed that male workers who had been exposed to cumulative lifting loads of 5 -21.5 ×10 6 Nh exhibited a 1.7-fold higher risk of disk protrusion compared to those exposed to loads of 0 -<5 ×10 6 Nh, suggesting that cumulative effects of all lifting loads, without a threshold, on disk protrusion [5][6][7]. In a later study [8], participants who had been exposed to a high lifting load (≥8.9 ×10 6 Nh) exhibited an OR of 2.2 for disk protrusion compared to those exposed to a low lifting load (<4.9 ×10 5 Nh). This last study also assumed no per lift threshold for the accumulated load.…”
Section: Discussionmentioning
confidence: 96%
“…They showed that male workers who had been exposed to cumulative lifting loads of 5 -21.5 ×10 6 Nh exhibited a 1.7-fold higher risk of disk protrusion compared to those exposed to loads of 0 -<5 ×10 6 Nh, suggesting that cumulative effects of all lifting loads, without a threshold, on disk protrusion [5][6][7]. In a later study [8], participants who had been exposed to a high lifting load (≥8.9 ×10 6 Nh) exhibited an OR of 2.2 for disk protrusion compared to those exposed to a low lifting load (<4.9 ×10 5 Nh). This last study also assumed no per lift threshold for the accumulated load.…”
Section: Discussionmentioning
confidence: 96%
“…The most surprising outcome of this study is probably that strong evidence was found that age, gender, body weight, BMI, smoking, car driving, the type of occupation (ie, working as a nurse or construction carpenter) nor recreational activities at leisure time were associated with the progression of DD. This was unexpected, as several studies show that heavy physical activity or work and smoking are key factors in the onset of DD . For smoking, however, there is one high‐quality study (out of five) that finds that smoking during follow‐up to a greater reduction in disc height .…”
Section: Discussionmentioning
confidence: 99%
“…show that heavy physical activity or work and smoking are key factors in the onset of DD. 11,[54][55][56] For smoking, however, there is one highquality study (out of five) that finds that smoking during follow-up to a greater reduction in disc height. 42 This is in contrast to a study by the same authors 2 years earlier, in which they found that smoking did not have any effect on the change in degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations